Improving Learning Outcomes of Slow Learners Through Differentiated Instruction and Scaffolding in Inclusive Classrooms - Panicker, Rasika (Digital Repository of Theses, 2026)
This dissertation investigates the impact of Differentiated Instruction (DI) and Scaffolding on improving learning outcomes of slow learners in inclusive classrooms within a semi-urban Indian context. Grounded in Vygotsky’s Zone of Proximal Development and Tomlinson’s (2017) Differentiated Instruction Model, the study integrates pedagogical and strategic management frameworks such as the Balanced Scorecard (Kaplan & Norton, 1996), Kotter’s 8-Step Change Model, and the Resource-Based View to connect classroom innovation with institutional sustainability. A mixed-methods research design was implemented at Rosary High School, Badlapur, involving 172 students (including 19 identified slow learners from Grades 5–8) and 10 teachers. Over a 16-week intervention cycle, teachers employed tiered tasks, visual aids, peer collaboration, and guided scaffolding. Quantitative data from pre- and post-test academic scores were supported by qualitative evidence from observations, student reflections, and teacher interviews. Findings revealed a 31.73 percent overall improvement in student achievement, with significant gains in Science (+15.74 points), Mathematics (+12.47 points), and English (+10.05 points). Cohen’s d values exceeded 3.5 across all subjects, indicating a very large effect. Qualitative data confirmed heightened motivation, confidence, and classroom participation among learners, along with improved teacher collaboration and reflective practice. Beyond pedagogical gains, the study demonstrates that inclusive teaching serves as a low-cost, high-impact business strategy for semi-urban schools. It strengthened institutional performance across the Balanced Scorecard dimensions: learning and growth, internal processes, stakeholder satisfaction, and financial efficiency. Improved academic credibility enhanced parental trust and word-of-mouth admissions, directly contributing to enrolment stability and institutional sustainability. The model thus positions inclusive pedagogy as both an ethical and strategic lever for long-term organisational growth in the education service sector.